Wujud Rancangan Arsitektur pada Perhelatan Pameran Instalasi Bambu Ditinjau dari Elemen Tata Atur - Maria Vika Wirastri; Nathania (ATRIUM: Jurnal Arsitektur, 2024)
Title: The Form of Architectural Design in Bamboo Installation Exhibition Examined from the Ordering Elements In architectural practice, art installation exhibitions serve as a platform for visual communication between designers and the public, aiming to garner appreciation and achieve specific goals and objectives through the works. This study examines 18 rice field hut objects created and exhibited at the Archifarming 2023, an exhibition featuring bamboo installations designed by architectural practitioners and handed over to local farmers. Recognizing the importance of applying ordering elements in architectural design, this research explores design forms using one of the design theories, namely ordering systems, which encompass function, space, geometry, link, and enclosure. Combining observation and analysis of supporting literature, the data is processed descriptively, evaluatively, and comparatively to identify similarities and differences in each aspect. The dominant ordering element used in the Archifarming 2023 installation is geometry, and upon further research, there are interrelations between the ordering elements that are crucial to creating harmony in design. Additionally, utilizing bamboo as the primary material enhances insights into natural materials and locality aspects. These findings also offer new perspectives on architectural design development in art exhibitions, contribute to design practices, and stimulate sustainability considerations in improving the quality of bamboo installation exhibitions for architects, designers, exhibition curators, and the wider community.